Motion capture in humanoid model with Unity engine using Kinect V2 - Amir Mahmud Husein; Jimmy Ciawi (Information Technology and Science (ITScience), 2021)
Animation is a technique to create illusion of motion, which is created by displaying a series of motionless pictures in sequence or using a spine/bones to create motion that looks real. All this time, the process of creating an animation still using traditional technique which requires special skills and take some time to finish a complicated animation which is used in movies or video games. Motion capture is an animation-making technique by tracking every part of body in order to find position and rotation of human’s joints which is generated by the image from the sensor. Motion capture has lots of method, such as marker base technique which use mark to track any motions. Motion capture markerless method that can capture or track motions without using any marks. Motion capture with markerless technique can be done by using RGB-Depth’s camera censor, which is by using Microsoft Kinect V2 with Kinect V2 SDK in order to make Kinect connected with computer, and using Unity Engine, a game engine that has already provided animation timeline and supports any 3D format which contains animation file that can be used in mostly other models which is using humanoid. In order to obtain motion data which will be changed into skeleton joint data, we will use connector OpenNI and 3D Collada model with (.dae) format because Collada is 3D format Open Source which is built using XML-based so that it can easily read and written back into 3D file as an output.